REFORMULASI BATAS USIA KEHAMILAN AKIBAT PEMERKOSAAN SEBAGAI SYARAT TINDAKAN ABORSI - Alvira Damayant; Ade Adhari (Fakultas Hukum Universitas Tarumanagara, 2021)
One of the most highlighted sexual harrasment case in the recent time, is the rise of rape against teenager and minors. Most of the victims will experience trauma, psychological disorder and even cause an abortion. The issues in this research is why the gestational age limit as a requirement for Abortus Provocatus Criminalis needs to be revised The research method used is empirical research. Based on the result of this research is that Article 76 letter (a) of the Health Law s an article that needs to be revised by the government. Because for rape victims, 6 weeks is a very short time to provide protection for rape victims to be able to have an abortion.